Estimation of glycaemic control in the past month using ratio of glycated albumin to HbA1c. Issue 7 (2nd May 2018) - Musha, I.; Mochizuki, M.; Kikuchi, T.; Akatsuka, J.; Ohtake, A.; Kobayashi, K.; Kikuchi, N.; Kawamura, T.; Yokota, I.; Urakami, T.; Sugihara, S.; Amemiya, S.; et al.
Abstract: Aims: To evaluate comprehensively the use of the glycated albumin to HbA1c ratio for estimation of glycaemic control in the previous month. Methods: A total of 306 children with Type 1 diabetes mellitus underwent ≥10 simultaneous measurements of glycated albumin and HbA1c . Correlation and concordance rates were examined between HbA1c measurements taken 1 month apart (ΔHbA1c ) and glycated albumin/HbA1c ratio fluctuations were calculated as Z‐scores from the cohort value at enrolment of this study cohort (method A) or the percent difference from the individual mean over time (method B). Results: Fluctuations in glycated albumin/HbA1c ratio (using both methods) were weakly but significantly correlated with ΔHbA1c, whereas concordance rates were significant for glycaemic deterioration but not for glycaemic improvement. Concordance rates were higher using method B than method A. Conclusions: The glycated albumin/HbA1c ratio was able to estimate glycaemic deterioration in the previous month, while estimation of glycaemic improvement in the preceding month was limited. Because method B provided a better estimate of recent glycaemic control than method A, the individual mean of several measurements of the glycated albumin/HbA1c ratio over time may also identify individuals with high or low haemoglobin glycation phenotypes in a given population, such as Japanese children with Type 1 diabetes, thereby allowing more effective diabetes management. What's new?: An increase in glycated albumin to HbA1c ratio can estimate deterioration in glycaemic control in the previous month, especially if the percent change in glycated albumin/HbA1c ratio from the individual mean value is used. The glycated albumin/HbA1c ratio Z‐score can identify individuals with high or low haemoglobin glycation phenotypes using reference data in Japanese children with Type 1 diabetes mellitus.